The transcatheter aortic valve implementation (TAVI)—a qualitative approach to the implementation and diffusion of a minimally invasive surgical procedure. (December 2015) - Merkel, Sebastian; Eikermann, Michaela; Neugebauer, Edmund; von Bandemer, Stephan
Abstract Background The transcatheter aortic valve implantation (TAVI), a minimally invasive surgical procedure to treat patients with severe symptomatic aortic stenosis, showed a rapid diffusion in Germany compared to the international level. The aim of this study is to identify and analyze factors affecting the implementation and diffusion of the procedure in hospitals using a qualitative application of the diffusion of innovations theory. Methods We conducted problem-centered interviews with cardiologists and cardiac surgeons working in German hospitals. The multi-level model "diffusion of innovations in health services organizations" developed by Greenhalgh et al. was used to guide the research. Data was analyzed using content and a thematic analysis. Results Among the ten participants who were interviewed, we found both barriers and facilitators related to the innovation itself, system readiness and antecedents, communication and influence, and the outer context. Key issues were the collaboration between cardiologists and cardiac surgeons, reimbursement policies, requirements needed to conduct the procedure, and medical advantages of the method. Conclusions The findings show that there are multiple factors influencing the diffusion of TAVI that go beyond the reimbursement and cost issues. The diffusion of innovations model proved to be helpful in understanding the different aspects of the uptake of the procedure. A central theme that affected the implementation of TAVI was the collaboration and competition between involved medical departments: cardiology and cardiac surgery. Against this background, it seems especially important to moderate and coordinate the cooperation of the different medical disciplines.